For the Sake of the Church: A Protestant-Reformed Practical Theological Perspective from the Netherlands - Schaeffer, Hans (International journal of practical theology, 2023)
In this article practical theologians from three Dutch Protestant institutions reflect on developments in the field. Their institutions started as ministry training centers and still have a strong focus on ecclesial practices. This focus has been reinforced by international trends in Practical Theology, mainly by a gradual shift towards an empirical way of working, with an emphasis on participative methods and ethnography. However, the field in the Netherlands continues to have a strong connection with church history and systematic theology. The authors discern three themes that characterize their institutes’ contribution to the international conversation on PT: the divine action within the practices, God’s promises in the context of his covenant, and a realistic view of brokenness, sin, and failure.